The heterogeneity of poverty. The case of Montevideo - Fuben Kaztman (CEPAL Review, 1989)
The economic crisis suffered during the present decade by the Latin American countries reduced the wages and incomes of many families, with a consequent deterioration in the living conditions of the affected population. Homes which had previously met the minimum conditions for ensuring the social integration of their members sank into poverty, thus increasing the heterogeneity of this phenomenon.